The Relevance of Nutrition for Pediatric Allergy and Immunity - Van Neerven, RJ Joost; Ruinemans-Koerts, Janneke (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The topics covered in this Special Issue range from breastfeeding and early-life nutrition to effects on microbiota, infection, allergy, asthma, and the mechanisms of immunomodulation via (the early introduction of) nutrition on infections and the development of (food) allergies.